SIMULASI DAN PEMODELAN TURBIN ANGIN TIPE DARRIEUS DENGAN KONFIGURASI ROTOR TIPE H UNTUK PEMBANGKIT LISTRIK TENAGA BAYU SKALA MIKRO - Alexander Widodo; Stenly Tangkuman; Hengky Luntungan (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2019)
The purpose of this study was to obtain the results of modeling and simulation for H-Darrieus wind turbine with straight blades. There are two approaches used in this study, namely hand calculation and software analysis. The calculation and analysis employed wind speed data of Manado City. Before applying software analysis, the data is processed to obtain the lift & drag forces that occur in turbine blades and other forces acting on wind turbines. Furthermore, the results of hand calculations and software analysis are compared so that the results of modeling and simulation are validated.The average counted-power of turbine is 181,81 watts, the wind turbine diameter is 2260 mm, and the wind turbine height is 2350 mm. The lift force is 143,257 N & the drag force is 3,978 N which is based on the attack angle 8,95, and the maximum Von Mises stress in the wind turbine is 184,96 MPa. Therefore, the wind turbine would not fail because the maximum stress that occurs in the structure is smaller than allowable stress of the material.Finally, the results of the modeling and simulation for the H-Darrieus wind turbine with straight blades are successfully obtained. The output of this research is turbine design drawings.Keywords: Darrieus Wind Turbine, Modelling, Simulation, Lift & Drag Force